Síndrome de túnel carpiano en el embarazo. Revisión de literatura y presentación de un caso clínico - Cerda A., Lorena; Contreras S., Mª Soledad (Revista Hospital Clínico Universidad de Chile, 2015)
Carpal tunnel syndrome (CTS) is the most common peripheral neuropathy in the general population. In pregnant women the prevalence increases to 31-62 % probably by edema secondary to the hormonal changes of pregnancy. The definitive treatment is surgical decompression, but in pregnant reserves only in exceptional cases where other treatments have failed. This population receives mainly conservative therapy consisting of splints, physical therapy and infiltration. Objective: To review the management of CTS in pregnant about a case. Methods: The clinical case of a pregnant patient with CTS managed conservatively was revised, based on this existing literature was reviewed. Results: 32 years old woman, studying 18 weeks pregnancy, consultation by paresthesia and loss of strength of both hands since1.5 months, more than right. Physical examination was consistent with bilateral CTS. Use of night splint is indicated. The electrodiagnostic evaluation reporting neuropathic sensitive-motor commitment severe intensity, subacute bilateral median nerve, with moderate denervation. Patient with symptoms persist, it is decided to perform infiltration of carpal tunnel steroid with good clinical and electrophysiological response. Conclusions: This case exemplifies the conservative treatment of CTS in pregnancy delivered good results. The literature supports the use of splints and steroid injections in this population.